If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + -3) = 4n + -8 Reorder the terms: 2(-3 + n) = 4n + -8 (-3 * 2 + n * 2) = 4n + -8 (-6 + 2n) = 4n + -8 Reorder the terms: -6 + 2n = -8 + 4n Solving -6 + 2n = -8 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -6 + 2n + -4n = -8 + 4n + -4n Combine like terms: 2n + -4n = -2n -6 + -2n = -8 + 4n + -4n Combine like terms: 4n + -4n = 0 -6 + -2n = -8 + 0 -6 + -2n = -8 Add '6' to each side of the equation. -6 + 6 + -2n = -8 + 6 Combine like terms: -6 + 6 = 0 0 + -2n = -8 + 6 -2n = -8 + 6 Combine like terms: -8 + 6 = -2 -2n = -2 Divide each side by '-2'. n = 1 Simplifying n = 1
| 2.05=0.9X-6.5 | | 2(5x-1)=3(x+11) | | 9x=3(7x+28) | | 8z=14 | | 8x-2(9-x)=6 | | 4y^2+9x-9=0 | | 5(2x-7)=-65 | | -8t-9=-41 | | 9-0.75(x+8)-5=-2 | | 8x^2-2x-3=0 | | 5(5x-3)+8=-4 | | -2(x-7)+4=24 | | 3x+9=-7 | | 81m^2n^2+18mn+1=0 | | x^2+11x+18=0 | | 11(x-5)=-4-7 | | 5-0.5(b-6)=4 | | 4n+12=4 | | 9=3(X-4)-(X-7) | | 2x-3+5=x+15 | | 25x^2-40xy+16y^2=0 | | 7y+3=-11 | | 7+2(x+1)=-2x+9 | | 9x-9=7x+39 | | 2p+13=-7 | | x-3=12-4x | | 5x+7=2x+3 | | 12(5-x)=48 | | 18-6x=-8x+14 | | 16-9y^2x^4=0 | | 6(8-4x)+10x-6=-28 | | -P=29 |